Histopathological and ultrastructural studies of Myxobolus turpisrotundus from allogynogenetic gibel carp Carassius auratus gibelio in China - Guo, Qingxiang; Zhai, Yanhua; Gu, Zemao; Liu, Yang (Folia parasitologica, 2016)
During an ongoing systematic survey on species diversity of myxozoans parasitising allogynogenetic gibel carp Carassius auratus gibelio (Bloch) in China, plasmodia were detected in the fins, lip, jaw, gill chamber, gill arches, operculum and oral cavity of infected fish. Combining the morphological and molecular data, the present species was identified as Myxobolus turpisrotundus Zhang, Wang, Li et Gong, 2010. Histopathological examination revealed that despite infecting different organs, M. turpisrotundus always occurred in dermis, demonstrating its affinity to this tissue. Histopathological effect of M. turpisrotundus on the host is relatively mild except parasites in the gill arches producing compression of the adipose tissue and heavy adductor muscles deformation with lymphohistiocytic infiltrates. In addition, the plasmodia in different sites were with the same complex structure arrangement: cup-like cells with unknown derivation, a thin collagenous fibril layer, areolar connective tissue, basement membrane and host epithelial cell. Ultrastructural analysis showed that the parasite has monosporic pansporoblast and sporogenesis followed the usual pattern of most of the myxosporeans.
Keywords: Animals; nemoci ryb; parazitární nemoci u zvířat; zvířata; Fish Diseases; Parasitic Diseases, Animal; Myxobolus; karas zlatý; China; Čína; Goldfish